1996
DOI: 10.1093/chemse/21.2.181
|View full text |Cite
|
Sign up to set email alerts
|

45-KDa GTP-binding Protein from Rat Olfactory Epithelium: Purification, Characterization and Localization

Abstract: The rat olfactory epithelium contains a specific water-soluble 45-kDa protein. This protein is recognized by anti-peptide antibodies which react with alpha-subunits of the known G-proteins. The 45-kDa protein has been isolated using DEAE-chromatography and gel-exclusion chromatography. The content of 45-kDa protein is about 2% of the total soluble proteins of the olfactory mucosa and it is located at the mucociliary surface. According to photo-affinity labeling, the 45-kDa protein possesses a high affinity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…These results are consistent with a previous report that the rat homologue of the Sec14l3 transcript is expressed in the surface layers of the trachea and in the ciliated bronchial epithelium in the lung [17]. The results of our ISH experiments extend the cell types known to express Sec14l3 from sustentacular cells of the olfactory mucosa [17,18] to include ciliated cells in lung bronchial/ bronchiolar epithelia (Fig. 2).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with a previous report that the rat homologue of the Sec14l3 transcript is expressed in the surface layers of the trachea and in the ciliated bronchial epithelium in the lung [17]. The results of our ISH experiments extend the cell types known to express Sec14l3 from sustentacular cells of the olfactory mucosa [17,18] to include ciliated cells in lung bronchial/ bronchiolar epithelia (Fig. 2).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, sustentacular cells in the rat nasal mucosa secrete the 45-kDa Sec14l3 protein, which forms part of the extracellular matrix in the mucus layer of the mucociliary surface of rat olfactory epithelium [18]. Moreover, COS-1 cells transduced with a Sec14l3 expression vector similarly excrete the Sec14l3 protein into the culture medium [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, protein p45 had been isolated from the rat olfactory epithelium and identified as a GTP-binding protein, which also exhibits GTPase activity [2]. The content of protein p45 was shown to be about 2% of all water-soluble proteins of the olfactory epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…The protein was detected at the highest concentrations in the surface layers of tissues that are in direct contact with environment [3]. Moreover, the protein was localized in secretory vesicles of cells of these tissues, as well as in the secretes released by cells into extracellular space [1][2][3]. Our experiments with the expression of p45 cDNA in COS-1 eukaryotic cells (unpublished data) indicated that protein p45 is accumulated in secretory vesicles and extracellular space, a culture medium for transfected cells.…”
Section: Introductionmentioning
confidence: 99%